2003
DOI: 10.1074/jbc.m208544200
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast Differentiation by Transforming Growth Factor-ॆ1 Is Dependent on Cell Adhesion and Integrin Signaling via Focal Adhesion Kinase

Abstract: Myofibroblast differentiation and activation by transforming growth factor-beta1 (TGF-beta1) is a critical event in the pathogenesis of human fibrotic diseases, but regulatory mechanisms for this effect are unclear. In this report, we demonstrate that stable expression of the myofibroblast phenotype requires both TGF-beta1 and adhesion-dependent signals. TGF-beta1-induced myofibroblast differentiation of lung fibroblasts is blocked in non-adherent cells despite the preservation of TGF-beta receptor(s)-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
508
5
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 556 publications
(550 citation statements)
references
References 41 publications
31
508
5
6
Order By: Relevance
“…Our studies in human lung fibroblasts have demonstrated that early and rapid activation of p38 MAPK by TGF-β1 is essential for the production of an autocrine growth factor that mediates activation of the PI3K-AKT pathway [8]. Additionally, our prior studies have demonstrated delayed, but sustained, activation of FAK that is required for stable induction of myofibroblast differentiation by TGF-β1 [12]. A specific requirement for SMAD3-dependent signalling in the activation of FAK and AKT, potential crosstalk between SMAD-dependent and -independent signalling, or their role (s) in the anoikis-resistance of myofibroblasts have not been previously reported.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Our studies in human lung fibroblasts have demonstrated that early and rapid activation of p38 MAPK by TGF-β1 is essential for the production of an autocrine growth factor that mediates activation of the PI3K-AKT pathway [8]. Additionally, our prior studies have demonstrated delayed, but sustained, activation of FAK that is required for stable induction of myofibroblast differentiation by TGF-β1 [12]. A specific requirement for SMAD3-dependent signalling in the activation of FAK and AKT, potential crosstalk between SMAD-dependent and -independent signalling, or their role (s) in the anoikis-resistance of myofibroblasts have not been previously reported.…”
Section: Discussionmentioning
confidence: 78%
“…Our previous studies showed that AKT activation by TGF-β1 in human lung fibroblasts is dependent on early p38-MAPK [8]. Additionally, FAK activation by TGF-β1 is mediated via a transcription-dependent process that is associated with upregulation of fibronectin and its integrin receptor subunits [12]. Crosstalk between these two pro-survival pathways and the specific role(s) of SMAD3, a key regulator of TGF-β1 pro-fibrotic signalling [24], in the delayed activation of FAK and AKT have not been defined.…”
Section: Tgf-β1-induced Fak But Not Akt Activation Is Dependent On mentioning
confidence: 99%
See 2 more Smart Citations
“…In those mice, alveolarization is delayed, but they finally form normal lungs (Sonja Mund and J.C.S., unpublished results). The alterations in cellular number and phenotype seen in older mutant lungs could in principle be a secondary consequence of the ECM alterations present at P1 (e.g., McGowan and Torday, 1997;Neptune et al, 2003;Thannickal et al, 2003); or could reflect an independent requirement for ephrinB2 function.…”
Section: Ecm Differences Precede Cell Number Changes In P1 Mutant Lungmentioning
confidence: 99%